2014
DOI: 10.1021/op500108m
|View full text |Cite
|
Sign up to set email alerts
|

Fluorophosphonylated Monomers for Dental Applications

Abstract: International audienceThe synthesis of acrylate derivatives bearing a difluorophosphonic acid function has been realized by ring-opening reaction of oxacycles and alkylation of fluorinated carbanions. Their use in self-etch adhesives is reported. The resulting adhesives based on difluorophosphonic acid monomers provide significantly higher dentin shear bond strength (SBS) than the one based on phosphonic acid, mainly due to the presence of fluorine atoms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…1,4 However, the low pKa 2 value of phosphonic acid and the hydrolyzable phosphate or phosphoric acid could limit their use for medicinal applications. 5 To address these issues, the difluoromethylphosphonate (or difluorophosphonate, pCF 2 ) derivatives and difluorophosphonic acid have been considered as interesting candidates for pharmaceutical and biomaterials applications [5][6][7][8][9] due to their resistance toward enzyme degradation and water hydrolysis. 6,[10][11][12] Additionally, difluorophosphonic acid is a stronger acid than phosphonic or phosphoric acids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,4 However, the low pKa 2 value of phosphonic acid and the hydrolyzable phosphate or phosphoric acid could limit their use for medicinal applications. 5 To address these issues, the difluoromethylphosphonate (or difluorophosphonate, pCF 2 ) derivatives and difluorophosphonic acid have been considered as interesting candidates for pharmaceutical and biomaterials applications [5][6][7][8][9] due to their resistance toward enzyme degradation and water hydrolysis. 6,[10][11][12] Additionally, difluorophosphonic acid is a stronger acid than phosphonic or phosphoric acids.…”
Section: Introductionmentioning
confidence: 99%
“…10 As long-standing interest in our laboratory, we were pioneers in the development of pCF 2 -functionalized monomers and polymers as potent self etching primers for dental applications. 5,9 Recently, we reported well-defined pCF 2 -functionalized polymers synthesized by reversible additionfragmentation chain transfer polymerization, in which the pCF 2 group was not only introduced into the polymer backbone but also at the macromolecular chain-ends. 13 Most polymers bearing pCF 2 groups are based on poly(meth)acrylic backbones which are not degradable at physiological pH (7.4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They would be capable of forming stronger bindings with calcium ions, the main inorganic component of the dental hard tissue hydroxyapatite (HAp) and oxide surfaces than phosphate group. 27 Thanks to their good adhesive and biocompatible properties, we have successfully demonstrated that pCF 2 -functionalized (meth)acrylate monomers can be used as etching adhesive-primer for dental applications. [27][28][29] Besides, polymers bearing difluorophosphonic groups show a high proton conductivity for replacing perfluorosulfonic acid based polymer such as Nafion.…”
Section: Introductionmentioning
confidence: 99%
“…27 Thanks to their good adhesive and biocompatible properties, we have successfully demonstrated that pCF 2 -functionalized (meth)acrylate monomers can be used as etching adhesive-primer for dental applications. [27][28][29] Besides, polymers bearing difluorophosphonic groups show a high proton conductivity for replacing perfluorosulfonic acid based polymer such as Nafion. 30,31 However, up to now, only a few examples of pCF 2 group introduction in materials science were reported in the literature.…”
Section: Introductionmentioning
confidence: 99%